Effects of glucose, time and temperature on bacterial growth in urine - Cruz, Enrique de la (1971)
Sterile urine and buffer samples of pH 6.5, with or without glucose, were inoculated with either 104 or 106 organims (two strains of Escherichia coli and two of Protetis vulgaris) per ml and incubated at -10, 4, and 25 C. The subsequent growth was determined at 0, 2, 4 and 8 hours. In the absence of glucose, bacterial populations of these organisms never reached 105 bacteria per ml whell the initial inoculum was 104 organisms, regardless of time and temperature of incubation. In presence of glucose, populations higher than 105 were observed in all of the specimens at room temperature.